Acoustic partial discharge localization in refined, bleached and deodorized palm oil (RBDPO) based on the Savitzky-Golay and moving average denoising methods - Ahmad, Nur Darina; Azis, Norhafiz; Jasni, Jasronita; Md Rezali, Khairil Anas; Talib, Mohd Aizam; Nik Ali, Nik Hakimi; Kozako, Masahiro (Universiti Putra Malaysia Press, 2025)
This research describes an investigation on the localization of partial discharge (PD) in Refined, Bleached and Deodorized Palm Oil (RBDPO) with the applications of 2 denoising methods, namely Savitzky-Golay (SG) and Moving Average (MA). A needle-plane electrode setup was used to initiate the PD. The electrical PD signal measurement was carried out through the impedance matching circuit (IMC), and the acoustic PD signal was obtained by acoustic emission (AE) sensors. The AE sensors were attached to the tank’s surface, and pre-amplifiers were used to boost the acquired acoustic PD signal. A high-voltage AC supply initiated the PD within the test tank filled with RBDPO. Both electrical and acoustic PD signals were denoised by SG and MA methods. The 2 denoising methods were evaluated based on the signal-to-noise ratio (SNR), root mean squared error (RMSE) and correlation coefficient (CC) metrics. The denoised acoustic PD signals were then utilized in the time difference of arrival (TDOA) technique to perform PD localization. The SG was found to be more effective than the MA in denoising both the electrical and acoustic PD signals based on its low RMSE and high CC. The estimated PD source locations based on the SG-denoised acoustic PD signals are closer to the actual PD source than those derived from the MA-denoised signals.